Analysis of the Implementation of the Internal Quality Assurance System in Higher Education: A Case Study at the Bakti Asih Polytechnic, Purwakarta, Indonesia - Lia Yulianti; Lova, Nova Rati; Armiyanti; Sofyan Sauri (Community Medicine and Education Journal, 2024)
Universities establish policies, standards, and quality assurance instruments. The IQAS (internal quality assurance system) policy is the general direction and policy of higher education institutions in implementing quality assurance. IQAS standards are criteria used to assess the quality of higher education implementation. The IQAS instrument is a tool used to collect data and information to assess the quality of higher education implementation. This study aims to conduct an analysis and study of the implementation of the internal quality assurance system in higher education: a case study at the Bakti Asih Polytechnic, Purwakarta, Indonesia. This research uses a qualitative approach with a case study method. Research data was obtained through interviews, observation, and document analysis. Data obtained through interviews, observation, and document analysis were then analyzed qualitatively. Qualitative analysis is carried out by reducing data, presenting data, and drawing conclusions. Overall, the implementation of IQAS at the Bakti Asih Polytechnic Purwakarta has gone well. However, efforts are needed to improve the communication and socialization of IQAS, as well as regular monitoring and evaluation of IQAS.